2022
DOI: 10.3390/healthcare10101912
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mental Health and Hand Hygiene Practices in Adults with Hypertension and Diabetes during the COVID-19 Pandemic: The 2020 Korea Community Health Survey

Abstract: The preventive measures against the spread of COVID-19 have negatively impacted the mental health of people with chronic diseases. This cross-sectional study investigated the association between mental health and hand hygiene practices in patients with hypertension (HTN) and diabetes mellitus (DM) (n = 74,296) during the COVID-19 pandemic. Their anxiety about contracting COVID-19 and death, depression, and hand hygiene practices were compared to that of controls. Multiple logistic regression analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The above circumstances contributed to delays in diagnosis, management, or treatment of disease to some extent ( de Joode et al, 2020 ; Jazieh et al, 2020 ; Breast Screening Working Group (WG2) of the Covid-19 and Cancer Global Modelling Consortium et al, 2021 ). Patients with chronic diseases such as hypertension, dyslipidemia, diabetes, cerebrovascular disease, heart disease, or cancer–collectively referred to as patients with underlying medical conditions, who have a higher risk of developing serious illness due to COVID-19 ( Aggarwal et al, 2020 ; Dai et al, 2020 ; Liang et al, 2020 ; Zhou et al, 2020 ; Centers for Disease Control and Prevention, 2022c ) might experience psychological burden ( de Joode et al, 2020 ; Kayikcioglu et al, 2020 ; Wang Y. et al, 2020 ; Kim and Kim, 2022a , c ; Ozkan et al, 2022 ). For example, a retrospective study in the UK analyzed the impact of COVID-19 on patient-reported health outcomes at a 30-day follow-up after hospitalization for acute stroke ( Ozkan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The above circumstances contributed to delays in diagnosis, management, or treatment of disease to some extent ( de Joode et al, 2020 ; Jazieh et al, 2020 ; Breast Screening Working Group (WG2) of the Covid-19 and Cancer Global Modelling Consortium et al, 2021 ). Patients with chronic diseases such as hypertension, dyslipidemia, diabetes, cerebrovascular disease, heart disease, or cancer–collectively referred to as patients with underlying medical conditions, who have a higher risk of developing serious illness due to COVID-19 ( Aggarwal et al, 2020 ; Dai et al, 2020 ; Liang et al, 2020 ; Zhou et al, 2020 ; Centers for Disease Control and Prevention, 2022c ) might experience psychological burden ( de Joode et al, 2020 ; Kayikcioglu et al, 2020 ; Wang Y. et al, 2020 ; Kim and Kim, 2022a , c ; Ozkan et al, 2022 ). For example, a retrospective study in the UK analyzed the impact of COVID-19 on patient-reported health outcomes at a 30-day follow-up after hospitalization for acute stroke ( Ozkan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese views about personal cleanliness are substantially influenced by early schooling, cultural experiences with handwashing, and reciprocal tendencies in case of during and after emergency 3 . Korean individuals with hypertension and diabetes were more likely than those without these conditions to have sadness, concern about contracting COVID‐19 and suffering from it, and a lower inclination to practice good hand hygiene 4 . Another study attempted to create a context‐specific relationship from a regional viewpoint by outlining the sociodemographic and WASH factors in southern Punjab, Pakistan and explored that hand pumps and tank water were the main drinking water sources associated with stunting.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Korean individuals with hypertension and diabetes were more likely than those without these conditions to have sadness, concern about contracting COVID‐19 and suffering from it, and a lower inclination to practice good hand hygiene. 4 Another study attempted to create a context‐specific relationship from a regional viewpoint by outlining the sociodemographic and WASH factors in southern Punjab, Pakistan and explored that hand pumps and tank water were the main drinking water sources associated with stunting. Batool et al 5 In rural areas and small towns in South Africa inequitable access to WASH services is caused by high inequality, rising unemployment, and the Apartheid legacy of a segregated service delivery system.…”
Section: Introductionmentioning
confidence: 99%